Back-Channel Etched Double Layer In-W-O/In-W-Zn-O Thin-Film Transistors. (23rd July 2018) - Li, Zhen-Hao; Kuo, Po-Yi; Chen, Wen-Tzu; Liu, Po-Tsun
Abstract : The thin-film transistors (TFTs) with back-channel etched (BCE) type enable channel length to be narrow and reduce parasitic capacitances owing to its shorter overlaps between the gate and source/drain (S/D) electrodes. In this study, a high-performance BCE-type oxide thin-film transistor was proposed for investigation. A novel stacked double layer In-W-O (IWO) / In-W-Zn-O (IWZO) channel structure was fabricated and developed. Respectively, IWZO exhibits a high resistance to back-channel etching damage and IWO channel achieve a high mobility. The double layer IWO/IWZO TFTs are promising candidates for driving active matrix organic light-emitting diode (AMOLED) and high resolution display applications in the future. The double layer IWO/IWZO TFTs with S/D pattern by H2 O2 + KOH can exhibit the high-performance electrical characteristic. The field-effect mobility (µFE ) 21.1cm 2 /V-s, subthreshold swing (S.S.) 0.15 V/dec., threshold voltage (VTH ) -0.092 V, and on/off ratio 4.88×10 8 can be achieved.